Clinical Predictors of Novel Influenza A (H1N1) Infection in Korea - Kim, Choon Ok; Nam, Chung Mo; Lee, Duk-Chul; Han, Sang Hoon; Lee, Ji Won (Yonsei medical journal, 2010)
Pandemic influenza A (H1N1) virus has spread rapidly and prompt diagnosis is needed for successful treatment and prevention of transmission. We investigated clinical predictors, validated the use of previous criteria with laboratory tests, and evaluated the clinical criteria for H1N1 infection in the Korean population. We analyzed clinical and laboratory evaluation data from outpatient clinics at Severance Hospital in Seoul, Korea between November 11 and December 5, 2009. This analysis included a total of 828 patients. Of these, 372 (44.9%) patients were confirmed with H1N1 infection by real-time reverse transcriptase-polymerase chain reaction (RT-PCR). The most common and predictive symptom was cough (90.3%, OR 8.87, 95% CI 5.89- 13.38) and about 40% of H1N1-positive patients were afebrile. The best predictive model of H1N1 infection was cough plus fever or myalgia. The sensitivities, specificities, positive predictive values, and negative predictive values of our suggested criteria were 73.9%, 69.5%, 66.4%, and 76.6%, respectively. Cough was the most common independent symptom in patients with laboratory-confirmed H1N1 infection, and while not perfect, the combination of cough plus fever or myalgia is suggested as clinical diagnostic criteria. Health care providers in Korea should suspect a cough without fever to be an early symptom of H1N1 infection.